The Relationship Between Food Availability, Household Food Security, and the History of Infectious Diseases with the Incidence of Malnutrition in Toddlers - Aiman, Ummu; Agustiani, Witri; Indriani, Nur; Hijratulmarah, Hijratulmarah; Fuadi, Nurul (Riviera Publishing, 2024)
The aim of this study is to investigate and analyze the relationship between food availability, household food security, and history of infectious diseases with the occurrence of malnutrition in toddlers. The method used in this research is an analytical survey with a cross-sectional study design. The population in this study is toddlers aged 12-59 months in the disaster-prone area of Pantoloan, with a sample of toddlers aged 12-59 months. The results of the study show a significant relationship between food availability and the occurrence of malnutrition in toddlers (p = 0.000). This means that toddlers who do not have guaranteed food availability in the last 12 months have a greater risk of experiencing malnutrition. However, no significant relationship was found between a history of infectious diseases and the occurrence of malnutrition (p = 0.566), possibly due to the mild and non-persistent nature of malnutrition, which does not affect the toddlers' immune system. Furthermore, a significant relationship was found between household food security and the occurrence of malnutrition (p = 0.006). Many families still need to prioritize adequate nutrition for their family, thus improving access to food to meet nutritional needs is still necessary. The study implies a deeper understanding of the factors influencing malnutrition in toddlers in disaster-prone areas and provides a basis for the development of appropriate interventions to improve the nutritional status of toddlers. Efforts to improve food availability and household food security are expected to reduce the risk of malnutrition in toddlers in the area.